Pengaruh Pemberian Extra Virgin Olive Oil terhadap Jumlah Sel Granulosa dan Kadar 17 Î² Estradiol Tikus yang di Papar Rhodamin B - Fera Yuli Setiyaningsih; Pande Made Dwi Jayasa; Hidayat Sujuti; Diah Prabawati Retnani (Journal of Ners and Midwifery, 2018)
The use of dyes in food today is very apprehensive. Many foods contain dyes that are prohibited to be used in food. The addition of the dye will have an impact on health. The aim of this research was to know the effectiveness of the administration of extra virgin olive oil to the number of granulosa cell and 17Î² estradiol level of Rats exposed by rhodamin B. The design of this study was true experimental with post test approach of group design control. The subject of the study was 30 white mice Rattus novergicus in the age of 12 weeks weight average 220 grams and in healthy condition. Rats were divided into 5 groups. Control group without treatment, positive control treatment with rhodamine B 18 mg / 200gr. Treatment 1 administration of rhodamine B 18 mg / 200gr and EVOO (Extra Virgin Olive Oil) 1.5 ml / KgBB, treatment 2 rhodamine B 18 mg / 200gr and EVOO 3 ml / KgBB, treatment 3 rhodamine B 18 mg / 200gr and EVOO 4,5 ml / KgBB. The number of granulosa cells was determined by HE staining, the level of 17Î² estradiol with ELISA. The data was analyzed by Kruskal Wallis test, Spearman Rank and Simple Linear Regression with degree of significance Î± <0.05. The average number of granulosa cells and the lowest levels of 17Î² estradiol were found in the positive control group and the highest average was in the treatment group 3. There was one dose that could significantly increase granulosa cells and the beta estradiol levels compared with the treatment group the other with niali Î± <0.05. The administration of EVOO affected the number of granulosa cells and the levels of 17Î² estradiol in rats exposed by rhodamine B.